Religiosity and Conversion Therapy is Associated with Psychosocial Health Problems among Sexual Minority Men (SMM) in Nigeria - Ogunbajo, Adedotun (Journal of religion and health, 2022)
We investigated the associations between social marginalization, psychosocial health, and religiosity among sexual minority men (SMM) in Nigeria (N = 406). We conducted bivariate and multivariable logistic regression. Factors associated with reporting a history of conversion therapy at a religious institution were: being HIV positive, having depressive symptoms, reporting suicide thoughts, and reporting inability to access medical care. Factors associated with increased odds of agreeing that sex between two men was a sin were: residing in Plateau, being Muslim, and higher levels of internalized homophobia. Our findings support the need for LGBT-affirming religious doctrine, which has implications for the health of LGBT communities.